2020
DOI: 10.5382/econgeo.4700
|View full text |Cite
|
Sign up to set email alerts
|

Chlorite and Epidote Mineral Chemistry in Porphyry Ore Systems: A Case Study of the Northparkes District, New South Wales, Australia

Abstract: Propylitic alteration, characterized by the occurrence of chlorite and epidote, is typically the most extensive and peripheral alteration facies developed around porphyry ore deposits. However, exploration within this alteration domain is particularly challenging, commonly owing to weak or nonexistent whole-rock geochemical gradients and the fact that similar assemblages can be developed in other geologic settings, particularly during low-grade metamorphism. We document and interpret systematic spatial trends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Chlorite, like illite, shows systematic variations in its chemical composition, which are related to the formation temperature. This has allowed the development of several useful geothermometers [20][21][22][24][25][26][27]29,30] since the 1980s (see below), which have been widely adopted in many studies on hydrothermal alteration in active and fossil hydrothermal systems [13,14,[19][20][21]38,[50][51][52][53][54][55][56][57][58][59]].…”
Section: Chloritementioning
confidence: 99%
“…Chlorite, like illite, shows systematic variations in its chemical composition, which are related to the formation temperature. This has allowed the development of several useful geothermometers [20][21][22][24][25][26][27]29,30] since the 1980s (see below), which have been widely adopted in many studies on hydrothermal alteration in active and fossil hydrothermal systems [13,14,[19][20][21]38,[50][51][52][53][54][55][56][57][58][59]].…”
Section: Chloritementioning
confidence: 99%
“…This would maintain lower fluid/rock ratios and higher temperatures to greater distances, clearly impacting the distribution of isotopic signatures, and can explain much of the heterogeneity we observe in the isotope data reported here. It is assumed that a mixing interface with external ground waters must occur at some point but we conclude this is located at edge of the zone of mineral chemical anomalism, now known to extend several km away from porphyry centers (e.g., Cooke et al, 2014;Wilkinson et al, 2015;Pacey et al, this volume).…”
Section: Additional Evidence For Magmatic Fluid Predominance: Based On the Oxygen And Hydrogen Isotope Resultsmentioning
confidence: 76%
“…Indeed, the spatial coincidence between propylitic alteration and whole rock base metal geochemical anomalies surrounding porphyry deposits has long been observed (e.g., Jerome, 1966;Cox et al, 1975;Jones, 1992;Zaluski et al, 1994;. Only recently though have trace element studies shown that a range of elements are present at elevated concentrations in the propylitic minerals themselves (Cooke et al, 2014;Pacey et al, this volume). Some of these elements are typical porphyry pathfinder elements (Mn, Zn, Pb, Cu, Sb, As and Bi) inferred to be ultimately derived from magmatic fluids.…”
Section: Introductionmentioning
confidence: 99%
“…The CE alteration which occurs exclusively along the margin of the Jindong granitoids (Choi, 1998;Heo et al, 2003) indicates that the alteration is strongly associated with the intrusions. A CE alteration can be formed either by a convection of external fluids driven by magmatism (Seedorff et al, 2005;Ayuso et al, 2010;Sillitoe, 2010), or by a cooled magmatic fluids (Orovan et al, 2018;Pacey et al, 2020). The geochemical studies on the alteration minerals (e.g.…”
Section: Origin Of Alterations and Ore Mineral Assemblagesmentioning
confidence: 99%